Genocide over the Serbian People in the Independent State of Croatia (1941–1945) - Dimić, Ljubodrag (Napredak, 2022)
From its very establishment in 1918, the Yugoslav state strived to be the state of “reconciliation”. That is why the crimes over Serbs perpetrated by Austria-Hungary were not largely emphasized in the Kingdom of Serbs, Croats and Slovenes / Yugoslavia, particularly not the crimes by Croats in occupation units, but conscientious researchers have still left their testimonies about them (see Reiss, 2019). For the sake of “reconciliation”, nothing was said about the genocide over the Serbian people in WW2 in the territory of the ISC. Because of the strategy of “keeping silent about the genocide”, crucially and for years, in the name of brotherhood and unity of Yugoslav nations, the topic did not have its place in the primary and secondary school curricula; the genocide crime perpetrated over the Serbian people was not discussed in history textbooks; for decades, it was not the topic in literature, while historians did not research the genocide crime or wrote substantially about it. However, if several generations of the representatives of the historian profession have an “alibi” for such behaviour, the generation of those writing in Serbian culture today must also take an attitude towards that sensitive topic. “To speak up” about the genocide over the Serbian people in the 20th century primarily means to write critically about the past times, with no passion, rationally and based on historical sources, “the way it really occurred”.
Keywords: genocide; Independent State of Croatia; racial laws; Serbs; Jews